2008
DOI: 10.1165/rcmb.2008-0047oc
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Rich Tyrosine Kinase 2 Regulates Spreading and Migration of Eosinophils after β2-Integrin Adhesion

Abstract: We examined the role of proline-rich tyrosine kinase (Pyk) 2 in the spreading and migration of human blood eosinophils after beta(2)-integrin ligation. Western blot analysis showed that Pyk2 was activated by phosphorylation at Y402 after eosinophil adhesion to BSA-coated plates after activation with IL-5, platelet-activating factor (PAF), formyl-met-leu-phe (fMLP), or Mn(2)(+). To determine the role of Pyk2 in regulating eosinophil migration, we used a transducable dominant-negative inhibitor of Pyk2, TAT-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…In contrast, Pyk2 positively regulates naive mouse CD8 T cell (17) and NK cell (20) adhesion to ICAM-1, and has no impact on neutrophil (16) or eosinophil (21) adhesion. Knockout or inhibition of Pyk2 enhances macrophage cell spreading (15); decreases cell spreading of naive T cells (17), B cells (22), eosinophils (21), and HL-60 cells (23); and has no effect on neutrophil spreading (16).…”
mentioning
confidence: 86%
“…In contrast, Pyk2 positively regulates naive mouse CD8 T cell (17) and NK cell (20) adhesion to ICAM-1, and has no impact on neutrophil (16) or eosinophil (21) adhesion. Knockout or inhibition of Pyk2 enhances macrophage cell spreading (15); decreases cell spreading of naive T cells (17), B cells (22), eosinophils (21), and HL-60 cells (23); and has no effect on neutrophil spreading (16).…”
mentioning
confidence: 86%
“…Pyk2 regulates the formation of lamellapodia and filapodia as well as chemotaxis to IL-5, PAF, and fMLP (18). The objective of this investigation was to determine if these prior preliminary observations would translate to reduction in AHR in an immune-sensitized mouse in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of the kinase-dead mutant of Pyk2 known to prevent Pyk2 enzymatic activity blocked IL-8-induced chemotaxis of HL-60-derived PMN-like cells (22). We have shown that while Pyk2 does not initiate endothelial adhesion of eosinophils, it is essential for eosinophil spreading and migration to various chemoattractants after b2 integrin adhesion in vitro (18). However, the role of Pyk2 in asthma and allergic inflammation in vivo is unknown.…”
mentioning
confidence: 82%
See 2 more Smart Citations